ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE OPERASI TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PERUSAHAAN SUBSEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016) - Fajar, Aulia; Hasan, Amir; Gusnardi, Gusnardi (Jurnal Tepak Manajemen Bisnis, 2018)
The main purpose of a company is to enhance the wealth of the ownerby maximizing firmâs value. But the failure to formulating a suitable strategyregarding the factors that affecting firmâs value often became the main cause thata company fail to maximizing itâs value. This research was conducted to analyzethe effect of profitability, firmâs size and operating leverage on firmâs value and todetermine wether capital structure is capable to mediate that effect. Thepopulation of this study are the plantation company that listed in Indonesia StockExchange (IDX), 10 samples was choosen with purposive sampling method. Thecriteria for the sampling method was that the company must be listed in IndonesiaStock Exchange during 2012-2016 period. Path analysis was used as the dataanalysis technique and SPSS as the data analysis software. The Researchconcluded that profitability and capital structure significantly affect firmâs value.Meanwhile, firmâs size and operating leverage had negative but insignificanteffect to firmâs value. Profitability and operating leverage showed negative andsignificant effect to capital structure. The mediating effect was shown by capitalstructure to the effect of profitability towards firmâs value but not for the effect offirmâs size and operating leverage for firmâs value.